Games as a didactic resource to develop a1 english level listening skills of eighth grade visually impaired students at unidad educativa José Antonio García Cando, school year 2021-2022 - Beltrán Lainez, Meline Xiomara (2021)
For several years, inclusion has been present in many aspects of society; so that all people have the same rights and obligations. This research aimed to promote the educational inclusion of people with visual impairment and create equal opportunities in learning English. In addition, to demonstrate that this disability is not a limitation in teaching and learning. In students with visual impairment, learning is better generated through playful activities that allow the development of the sense of hearing. For that reason, the objective of this research project is to emphasize and propose the importance of didactic games in the teaching of English as a foreign language, as well as the development of receptive skills in visually impaired students at Unidad Educativa José Antonio García Cando. A qualitative study was conducted with the participation of the principal of the institution, English teachers, a student with visual impairment, and a specialist in teaching students with this condition. The data were collected through the development of interviews; then, the interpretation of the information provided by the interviewees allowed the design of didactic games that fulfill the specific special needs of students with visual impairment.